OFDM and alternative waveforms - Demir, A. F.; Arslan, Hüseyin (Institution of Engineering and Technology, 2020)
This chapter aims to provide an in-depth understanding of orthogonal frequency division multiplexing (OFDM) as well as its performance in the presence of a multipath channel and various impairments. Also, major alternative waveforms, which provide better time–frequency localization compared to OFDM using various filtering/windowing approaches with certain trade-offs, are overviewed to present a complete picture of the waveform design discussions of next-generation wireless technologies. This chapter is organized as shown in Figure 2.1.
Keywords: OFDM; Alternative Waveforms; Electrical and Electronics